Evolução do tamanho corporal de Amazona (Aves: Psittacidae) em ilhas - Porto Netto, José Queiroz (2022)
The changes in insular species in which large-bodied species reduce its size (dwarfing) and small-bodied species increase their size (gigantism) is called the Island Rule. Available models to explain this differentiation seek to assess how species with different body sizes respond evolutionary to biotic and abiotic ecological factors on the islands. In this study, six characters were evaluated to verify the tendency of differentiation in body size and other morphological characteristics in insular species of parrots of the genus Amazona. The presence of this trend was evaluated comparatively by the Si ratio between the body size between the insular species and the presumed continental ancestor, defined from a phylogeny of the genus and accessed by a Phylogenetic Generalized Least-Squares (PGLS). We also evaluated the evolutionary processes involved in this change through evolutionary quantitative genetic models for the differentiation of Amazona guildingii, contrasting effects of genetic drift and natural selection. We found differences in body size in the continent/island transition, but not following the pattern expected by the island rule; the body size of Amazona species does not show a clear relationship between Si values and ancestral body size. For A. guildingii, we found that the character differentiation is explained by natural selection and not by genetic drift, especially for wing size and body mass. We conclude that the island rule pattern cannot be generalized to the genus Amazona, although there is evidence of natural selection acting on differentiating the body size generating insular gigantism.